Cargo work for maritime operations - House, D. J. (Elsevier/Butterworth-Heinemann, 2005)
Previously published as Kemp & Young's Cargo Work, this new edition has been fully revised and expanded to comprehensively reflect unit load containerised systems that are now used in the majority of cargo shipping, while retaining the necessary detail on transporting key classes of cargoes safely, efficiently and profitably. This is an essential reference for merchant seamen internationally.